Operating a patient medicines helpline: a survey study exploring current practice in England using the RE-AIM evaluation framework - Matt Williams; Abbie Jordan; Jenny Scott; Matthew D. Jones (BMC, 2018)
Abstract Background Patient medicines helplines provide a means of accessing medicines-related support following hospital discharge. However, it is unknown how many National Health Service (NHS) Trusts currently provide a helpline, nor how they are operated. Using the RE-AIM evaluation framework (Reach, Effectiveness, Adoption, Implementation, and Maintenance), we sought to obtain key data concerning the provision and use of patient medicines helplines in NHS Trusts in England. This included the extent to which the delivery of helplines meet with national standards that are endorsed by the Royal Pharmaceutical Society (standards pertaining to helpline access, availability, and promotion). Methods An online survey was sent to Medicines Information Pharmacists and Chief Pharmacists at all 226 acute, mental health, specialist, and community NHS Trusts in England in 2017. Results Adoption: Fifty-two percent of Trusts reported providing a patient medicines helpline (acute: 67%; specialist: 41%; mental health: 29%; community: 18%). Reach: Helplines were predominantly available for discharged inpatients, outpatients, and carers (98%, 95% and 93% of Trusts, respectively), and to a lesser extent, the local public (22% of Trusts). The median number of enquiries received per week was five. Implementation: For helpline access, 54% of Trusts reported complying with all 'satisfactory' standards, and 26% reported complying with all 'commendable' standards. For helpline availability, the percentages were 86% and 5%, respectively. For helpline promotion, these percentages were 3% and 40%. One Trust reported complying with all standards. Maintenance: The median number of years that helplines had been operating was six. Effectiveness: main perceived benefits included patients avoiding harm, and improving patients' medication adherence. Conclusions Patient medicines helplines are provided by just over half of NHS Trusts in England. However, the proportion of mental health and community Trusts that operate a helpline is less than half of that of the acute Trusts, and there are regional variations in helpline provision. Adherence to the national standards could generally be improved, although the lowest adherence was regarding helpline promotion. Recommendations to increase the use of helplines include increasing the number of promotional methods used, the number of ways to contact the service, and the number of hours that the service is available.